Performance Analysis of IC MPPT Algorithm for Applications of Solar PV in DC Microgrid - Kumar, Kunal; Kumar, Prince; Bohre, Aashish Kumar (SN computer science, 2023)
Solar Photovoltaic (PV) is an emerging source of energy and playing an important role in electrical power system. The I–V and PV characteristics of solar PV system are non-linear in nature, thereby it is difficult to extract the maximum power. The maximum power is extracted with the help of Maximum Power Point Tracking (MPPT) algorithms. In this paper, an algorithm for MPPT for the application of Solar PV in DC Microgrid (DCMG) based on the concept of Incremental Conductance (IC) has been implemented and studied. The assessment has been done by taking the consideration on I–V curve that exhibits the shifting of maximum power operating point (MPOP) on the I–V curve has been done by varying the duty ratio (DR). The comparative analysis has been done between the implemented IC algorithm and widely adapted algorithm of Perturb and observe (P&O) by considering varying irradiance conditions to validate the implemented algorithm of IC is best suited for DCMG application to provide quality electrical power supply. A stand-alone PV system is simulated in MATLAB R2021b Simulink platform with a DC–DC boost converter (DDBC), and an algorithm for both MPPT based on IC and P&O has been implemented to check the performance. The obtained results after simulation clearly exhibit the supremacy of the IC algorithm of MPPT of PV system, which can be used for quality performance to supply electrical power to DCMGs.